2020
DOI: 10.1210/clinem/dgaa889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Treatment Choice on 2-year Quality of Life in Patients with Low-risk Papillary Thyroid Microcarcinoma

Abstract: Context The long-term quality of life (QoL) in patients with low-risk papillary thyroid microcarcinoma (PTMC) underwent active surveillance (AS) and immediate surgery is unclear. Objective The aim of this study was to investigate the effect of initial treatment choice on 2-year QoL in patients with low-risk PTMC Design, Setting, and Participants We analyzed 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Both agree in the improvement of this parameter in subjects undergoing AS compared to the control group (patients undergoing thyroidectomy). However, it should be highlighted that both studies lack randomisation and have a short follow-up ( 18 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both agree in the improvement of this parameter in subjects undergoing AS compared to the control group (patients undergoing thyroidectomy). However, it should be highlighted that both studies lack randomisation and have a short follow-up ( 18 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we identified 20 studies reporting on physical HrQoL following TT or HT [ 18 , 34 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 67 , 68 , 70 , 73 ] ( Table 5 ). Eight studies compared postoperative TT HrQoL with community reference values using seven different QoL instruments (i.e., SF-36, MFI-20, ThyPRO, PSQI, Billewicz Score, visual analog scale, and 15D) [ 18 , 34 , 51 , 53 , 55 , 58 , 61 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies assessed postoperative physical-related HrQoL in comparison with patients undergoing active surveillance (AS) [ 54 , 60 , 67 ]. All three studies found a significant impairment in physical-related HrQoL for patients undergoing HT versus patients undergoing AS for at least one of the following items: global physical subscale ( n = 1), voice symptoms ( n = 1), trouble with concentration ( n = 2), neuromuscular symptoms ( n = 1), throat or mouth symptoms ( n = 2), feeling chilly ( n = 1), or problems with scar ( n = 2) [ 54 , 60 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations